Communication Strategies in Stunting Management Towards Healthy, Intelligent, and Cheerful Children - Husnul Khotimah; Nur Anisa Khadijah; Nova Khoirunnisa Witanti; Tasya Amelia Ramadhani; Ahmad Suriansyah; Ratna Purwanti (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
Stunting is a chronic nutritional problem that has long-term impacts on growth and development as well as the quality of human resources. One of the efforts to address stunting is through the implementation of effective communication strategies and synergy between schools, teachers, and parents. This study aims to describe and analyze the communication strategies of school principals, teachers' parenting patterns, and parents' parenting patterns in handling stunting towards healthy, intelligent, and cheerful children at Noor Latifah Kindergarten in Gambut District. This study uses a descriptive qualitative approach with a case study type. Data collection techniques were carried out through in-depth interviews, observations, and documentation. Data analysis uses the Miles and Huberman 2014 model, which includes data collection, data presentation, data reduction, and drawing conclusions. The research results show that school principals implement interpersonal, vertical, and diagonal communication, as well as social mobilization through partnerships with parents and community health centers. Teachers apply a collaborative educational parenting approach through promoting healthy living habits and meaningful learning, in collaboration with parents. Parents practice a democratic parenting style by ensuring proper nutrition, caregiving, and fostering healthy habits in their children at home. Effective and collaborative communication strategies are proven to support a holistic and integrative approach to stunting management.